Dynamic testing of volleyball players' body posture using a formetric 3D device. Issue 4 (24th November 2020) - Ying, Jianhua; Ren, Feng; Fekete, Gusztáv
Abstract : Volleyball activities involve several factors such as asymmetrical movements, muscle imbalance, and continual overloading that damage body posture. This study aimed to determine postural changes of volleyball players in spike overhand front set, overhand pass ball, and mat ball motions, and if there is any postural variation difference between short training and long training volleyball players. Methods: Fifteen long training and short training male volleyball players aged 21–23 years were recruited in this study. The upper‐thoracic angle, thoracic‐lumbar segment angle, lower lumbar‐sacral segment, pelvic inclination, and inclination of the acromion were measured using DIERS formetric 3D device in a dynamic way. During the overhand pass motion, long training participants showed a significant larger peak upper‐thoracic and peak thoracic‐lumbar angles than short training participants. During the mat ball motion, the long training volleyball players demonstrated a significant higher peak upper‐thoracic angle, but a smaller peak inclination of the acromion than short trainers. During the spike overhand front set motion, long trainers showed a significant smaller peak upper‐thoracic angle than short trainers. Athletes should consider developing an appropriate dynamic trunk stabilization to reduce posture imbalance during volleyball activities.